Desaign of Converter Hijri Calendar to Ad Calendar for Determaning Islamic Great Days Using Matlab - Muttaqi, Uzlifa Khanifatul (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2016)
This research is motivated by the importance of knowing an Islamic great day calendar on AD calendar. It was intended to answer the question: How to design converter Hijri calendar to AD calendar for determining Islamic great days using Matlab? The research used âdesignâ method, because it was one of activities to translate the result of analysis to software form and also used to develop an existing application. This application made by a Matlab software. Matlab was a conversion tool to determine Islamic great days. Data of this research was obtained from questionnaire. And all the questionnaire datum was used to design application. The technique of feasibility analysis application was obtained from a validation. It was using black-box method. The result showed that the application was made by three ways: First, making an appearance in GUI Matlab appropriate with interface design application. Second, entering the script in each menu of application. Third, entering JD formula in application that were already functioning. Â©2016 JNSMR UIN Walisongo. All rights reserved.